2017
DOI: 10.4236/jwarp.2017.911080
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Quality of Lake Kyoga at Selected Landing Sites and Anthropogenic Activities

Abstract: Lake Kyoga, one of the great African lakes in Uganda is facing an increasing pressure from human activities yet there is limited information on water quality of the lake. Therefore this study determined selected physico-chemical parameters of Lake Kyoga at some landing sites (Kayei, Acholi inn, Waitumba, Masindi port) and anthropogenic activities (boat dock, waste site, garden, fishing). The parameters included temperature, pH, water flow rate, dissolved oxygen (DO), nitrite ( 2 NO − ) and phosphate (PO 4 -P).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Acholi inn landing site had the overall highest mean coverage followed by Masindi port, Waitumba and finally Kayei ( Spearman's correlation of S. molesta coverage with selected physico-chemical parameters [38] showed significant positive correlation with PO 4 -P (r s = 0.27, p = 0.01, n = 96). This is supported by previous studies which established that growth rates of S. molesta increase with increase in nutrients (e.g.…”
Section: Salvinia Molesta Coverage At Landing Sites and Anthropogenicmentioning
confidence: 91%
See 3 more Smart Citations
“…Acholi inn landing site had the overall highest mean coverage followed by Masindi port, Waitumba and finally Kayei ( Spearman's correlation of S. molesta coverage with selected physico-chemical parameters [38] showed significant positive correlation with PO 4 -P (r s = 0.27, p = 0.01, n = 96). This is supported by previous studies which established that growth rates of S. molesta increase with increase in nutrients (e.g.…”
Section: Salvinia Molesta Coverage At Landing Sites and Anthropogenicmentioning
confidence: 91%
“…According to Wanda et al [7], the brittle stolons of S. molesta are easily broken by the movement of boats. Ongom et al [38] also reported that mixing of Lake Kyoga water increases the oxygen circulation in the lake. S. molesta weed coverage was the least in the fishing areas ( Figure 3) associated with low nutrient (PO 4 -P) concentrations (Figure 4) and the low weed coverage also resulted into increased dissolved oxygen concentrations at the fishing areas.…”
Section: Salvinia Molesta Coverage At Landing Sites and Anthropogenicmentioning
confidence: 96%
See 2 more Smart Citations
“…In this case, the concentration of phosphorus in the water is, on average, of 4.66 mg L -1 . This value indicates the hypertrophic condition in which the water is found (Moreno-Franco et al, 2010); domestic and industrial wastewater are the main source of phosphorus, as well as agricultural drainage, and its main characteristic is that it is composed of detergents that derive from anthropogenic activity (Lizárraga-Mendiola et al, 2013;Ongom et al, 2017) (Ayers & Westcot, 1985); in this case, the excess concentration of phosphate may be due to agricultural, domestic and industrial discharge (Velázquez-Machuca et al, 2010).…”
Section: Sampling Water Analysis and Statistical Analysismentioning
confidence: 99%